A resurgence of US manufacturing: Evidence and wishful thinking - Berend Diekmann (Intereconomics, 2013)
The US manufacturing sector is currently experiencing its most signifi cant upswing in 35 years, leading many politicians and economic analysts to claim that the US economy is being re-industrialised. While the notion of a renaissance of the industrial sector does not seem far-fetched, given that the US is experiencing a shale gas and oil boom, this will not necessarily translate into significantly higher outputs. Upon closer examination of some of the key indicators, it becomes evident that the facts do not yet bear out the claim of a resurgence of manufacturing in the US. Therefore, it may be premature to identify US industry as a newly superior global competitor to the EU.
Keywords: 330